Prevalence of Crohns Disease in Endoscopic Unit Cipto Mangunkusumo Hospital - Nata Pratama; Murdani Abdullah; Dolly Dolven Kansera; Jane Estherina; Rizki Yaruntradhani; Fransiska Hardi; Raden Nur Ista; Marcellus Simadibrata; Achmad Fauzi; Daldiyono Daldiyono; Abdul Aziz Rani; Diah Rini Handjari; Pamela Abineno (The Indonesian Society for Digestive Endoscopy, 2011)
Background: The cumulative number of inflammatory bowel disease patients in Asia has raised three times since early 1990s, although Crohn’s disease is still less common than ulcerative colitis. The objective of this study was to provide clinical and demographic data of Crohn’s disease patients seen in Endoscopic Unit Cipto Mangunkusumo Hospital and compare the Results with other Asian countries. Method: This study was done retrospectively cross-sectional descriptive from medical records of all patients underwent colonoscopy at Endoscopic Unit, Cipto Mangunkusumo Hospital, and histological evaluation in the Department of Anatomical Pathology, Faculty of Medicine, University of Indonesia, between 2007 and 2008. Data was analyzed using SPSS version 17. Results: Of 921 patients who underwent colonoscopy, 19 (2.1%) patients were diagnosed with Crohn’s disease. There was no sex preponderance. The mean age was 47.7 years with a peak age at presentation between 51 and 60 years. The main clinical complaints were diarrhea (42.1%), lower gastrointestinal bleeding (36.8%), abdominal pain (10.5%) and upper gastrointestinal bleeding (5.3%). Colonoscopic findings were hyperemia in 94.7%, edema in 57.9%, erosions in 63.2%, ulcerations in 89.5%, pseudopolyp in 31.6%, fragile lesion in 10.5%, stenosis, fistulation, and cobblestone appearance in 5.3%. Involvement of isolated left colon was 26.3%; other manifestations were isolated right colon (10.5%), pancolitis (57.9%), ileitis (5.3%), ileocolitis (36.8%) and skip lesion (5.3%). Conclusion: The prevalence of Crohn’s disease in this study was similar to the findings in previous studies in Asian countries, with diarrhea as the main clinical complaint, and pancolitis as the dominant finding in colonoscopy examination. Keywords: Crohn’s disease, prevalence, clinical complaints, colonoscopy description